Comparing the occurrence rate of gestational hypertension during pregnancy with frozen embryo transfer and natural pregnancy - Farideh Moramezi; Roshan Nikbakht; Najimeh Saadati; Elham Farhadi; Negin Raad (Journal of Family Medicine and Primary Care)
Introduction: Recent researches have indicated that pregnancies with frozen embryo transfer are associated with the increment of risk of maternal and neonatal complications, especially hypertension during pregnancy. The present study aimed to compare the occurrence rate of gestational hypertension in pregnancy with frozen embryo transfer and normal pregnancy. Materials and Methods: This research, as a retrospective cross-sectional study, was performed on pregnant women with frozen embryo transfer (n = 97) and women with normal pregnancies (n = 164) referring to medical centers under the supervision of Ahvaz University of Medical Sciences in 2021. Women aged 18–35 were included in the study after week 20th of pregnancy. Maternal and neonatal outcomes including hypertensive disorders of pregnancy (including gestational hypertension and preeclampsia), preterm birth (before the week 37th), low birth weight (lower than 2500 g), neonatal asphyxia (Apgar score >7 in minute 5th), intrauterine growth restriction (IUGR) and bleeding in the first trimester of pregnancy were evaluated. The association between frozen embryo transfer and pregnancy outcomes was evaluated using multiple logistic regressions. Results: The findings of this study indicated that pregnancy hypertension was observed in 23 people (23.7%) from the frozen embryo transfer group vs. 18 people (11.0%) from the normal pregnancy group (P = 0.006). Frozen embryo transfer pregnancy has a higher risk of gestational hypertension (OR = 2.521, 95% CI: 1.281-4.962; P = 0.007), preterm birth (OR = 2.264, 95% CI: 1.335-3.840; P = 0.002), and low birth weight (OR = 2.017, 95% CI: 1.178-3.455; P = 0.011). However, the incidence of birth asphyxia (P = 0.850), intrauterine growth restriction (P = 0.068), first-trimester bleeding (P = 0.809), and placenta accreta (P = 0.143) did not show a significant difference between two types of normal pregnancy and frozen embryo transfer pregnancy. Conclusion: Frozen embryo transfer pregnancy was associated with a higher risk of maternal and neonatal complications, hypertension, preterm birth, and low birth weight compared to natural and spontaneous pregnancies.